PERANCANGAN SISTEM KEAMANAN SMART ROOM BERBASIS INTERNET OF THINGS MENGGUNAKAN NODEMCU (STUDI KASUS: LAB. KOMPUTER IPTEK) - Mohamad Ramadhan Alzidani; Maulana Ardiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
ectronic devices today mostly still uses manual switches to disconnect and connect the electric current. In addition, several electronic devices already have their own control devices to make their use easier, but difficulties often occur if you want to control more than one electronic device, this is because the remote control can only control one electronic device. The more electronic devices to be controlled, the more remote controls are needed. To overcome this problem, it is necessary to design a system to control all electronic devices in one controller. The control device can take advantage of the communication media that is currently used on all Android smartphones, namely internet communication media. For this reason, through the integration of the internet network on android smartphone devices and the hardware and software used, ideas are generated to design internet-based electronic device control devices on android smartphones. And the author also adds an RFID system to this control device to control its electronic devices. The prototype design used in this study uses ESP8266, RFID, relay, solenoid lock and android smartphone. The system development in this study works according to the Internet of Things (IoT) concept. Users can control electronic devices directly